ILM, Star Wars e a transformação criativa dos efeitos visuais no cinema de Hollywood - Pavelqueires, Nubia Rossi (Universidade Federal de São Carlos, 2024)
This work investigates the evolution of workflows and visual effects (VFX) techniques applied by Industrial Light & Magic (ILM) in the first two Star Wars trilogies, aiming to analyze the main impacts of the transformation of the film industry from the digitization of VFX processes that were previously predominantly analog. It seeks to understand how ILM is an emblematic part of establishing standards for the creative conception and production of VFX in cinema, based on the question: "How did the transition from predominantly analog practices to digital methods and tools throughout the Star Wars film franchise influence the field of VFX within Industrial Light & Magic from its foundation to the beginning of the 21st century?". Through the comparative analysis of films, public interviews in the press, behind-the-scenes materials, and specialized bibliography on the specific historical and thematic scope addressed - such as authors Thomas G. Smith, Mark Cotta Vaz, and Richard Rickitt - the study examines how ILM innovated in each title driving the development of the film industry. The research comments on ILM's work in the use of new technologies and production processes to update the execution of multiple tasks involving visual effects by overcoming practical and creative challenges and expanding the narrative and sensory possibilities of cinema. From the analysis of the evolution of VFX techniques applied in Star Wars, the work demonstrates how ILM became a reference in the field of visual effects and a key player in the transition to digital cinema.
ILM, Star Wars and the creative transformation of visual effects in Hollywood cinema
Keywords: Star Wars; Efeitos visuais; ILM; Inovação tecnológica; Cinema digital; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::ADMINISTRACAO E PRODUCAO DE FILMES